2006
DOI: 10.3121/cmr.4.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Universal Pathogen-Reduced Plasma in Elective Open-Heart Surgery and Liver Resection

Abstract: ABO-incompatible transfusions and transfusion-related lung injury are today the leading transfusion-related causes of death in the developed world. Since anti-A and anti-B antibodies in plasma can give rise to serious, even fatal, transfusion reactions,ABO-identical/compatible plasma is indicated, but presents a logistical challenge and a risk for transfusion of incorrect plasma. In an effort to circumvent these problems, an ABO-independent universally applicable, pathogen-reduced plasma, Uniplas, has been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…25,28 Modern "pooled" universal plasma formulations (Uniplas, Octapharma Pharmazeutika, Austria; Bioplasma FDP, National Bioproducts Institute, Pinetown, South Africa) exist and contain a defined mixture of group A, B, AB, and O donor plasma with isohemagglutinin titers of less than 8 to less than 32 and acceptable transfusion safety. [29][30][31] Although extremely limited, our data suggest that mixed PPLTs, containing one WBD-PLT unit of recipient ABO type, could provide an additional layer of safety when out-of-group transfusion is unavoidable.…”
Section: Table 1 Anti-a and Anti-b Agglutinin Titer And Transfusion mentioning
confidence: 99%
“…25,28 Modern "pooled" universal plasma formulations (Uniplas, Octapharma Pharmazeutika, Austria; Bioplasma FDP, National Bioproducts Institute, Pinetown, South Africa) exist and contain a defined mixture of group A, B, AB, and O donor plasma with isohemagglutinin titers of less than 8 to less than 32 and acceptable transfusion safety. [29][30][31] Although extremely limited, our data suggest that mixed PPLTs, containing one WBD-PLT unit of recipient ABO type, could provide an additional layer of safety when out-of-group transfusion is unavoidable.…”
Section: Table 1 Anti-a and Anti-b Agglutinin Titer And Transfusion mentioning
confidence: 99%
“…Synopsis: Fifteen observational trials and seven RCTs were used to evaluate the safety of S/D plasma. No study reported an increase in AE in S/D plasma compared to conventional plasma and most reported a decrease.…”
Section: Product Efficacymentioning
confidence: 99%
“…PI has been used extensively in the manufacture of plasma protein fractions, and has all but eliminated transmission of infectious agents by these products [1]. In Europe, solvent‐detergent and methylene blue treatment have both been applied to plasma components, and psoralen treatment of platelets is being introduced in several countries [2–4]. Although solvent‐detergent‐treated pooled plasma has been approved for use in the USA and Canada, none of these methods has been adopted for single‐donor products in North America.…”
mentioning
confidence: 99%